Konsep Bagi Hasil Pada Akad Mudharabah: Studi Kasus Pada Bank Syariah - Sunarsa, Sasa; Anjani, Novia; Azizah, Salma Nur (STAI Al Musaddadiyah Garut, 2024)
Mudharabah Abstract is one of the most widely applied profit-sharing cooperation agreements by Islamic banks in Indonesia. However, in practice there are several problems related to the application of profit sharing in mudharabah contracts. This study aims to analyze the concept of profit sharing in mudharabah contracts in Islamic banking. The research method used is a case study on one of the Islamic banks in Indonesia. Data collection is carried out through interviews, observations, and documentation. Data analysis uses a qualitative descriptive approach. The results of the study show that the concept of profit sharing in the mudharabah contract in the Islamic bank is in accordance with sharia principles. Islamic banks apply the profit sharing ratio agreed at the beginning of the contract and divide profits according to the contribution of each party. However, there are several obstacles in its implementation, such as the difficulty of determining the real level of profit, the moral hazard of customers, and the lack of customer understanding of the concept of profit sharing. Keywords: Mudharabah, Profit Sharing, Sharia Banks